Aliphatic polyesteramide blend as well as preparation method and application thereof
By blending biodegradable alternating aliphatic polyester amides with different molecular weights and regularity in a certain proportion, the problem of difficult to take into account both mechanical properties and crystallization properties in the prior art is solved, and rapid molding and efficient production of materials are achieved.
Patent Information
- Application Number
- CN202311113558.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
AI Technical Summary
The existing biodegradable alternating aliphatic polyester amides are difficult to take into account both mechanical properties and crystallization properties, resulting in too long processing and molding time and low structural regularity.
By blending two biodegradable alternating aliphatic polyester amides with different molecular weights and regularity in a certain proportion, a biodegradable alternating polyester amide with improved crystallization properties and good mechanical properties was prepared.
It significantly shortens the processing and forming time, improves production efficiency, and while maintaining the original mechanical properties, it improves crystallization performance, making the material more suitable for use in a variety of application fields.
Smart Images

Figure BDA0004426161400000021 
Figure BDA0004426161400000041 
Figure BDA0004426161400000121
Abstract
Description
Technical Field The present invention relates to the field of polyester amides, and in particular to a biodegradable alternating aliphatic polyester amide blend, a preparation method thereof and an application thereof. Background Art Aliphatic polyester amide (PEA) is a new type of biodegradable polymer material. Compared with aliphatic polyester, the introduction of amide groups forms hydrogen bonds between amide groups, which makes the polymer have better mechanical properties. At the same time, the presence of ester bonds gives the material good biodegradability, making it have broad application prospects.
[0003] The alternating type polyester amide has a regular structure, a high melting point, a high degree of crystallinity, and good mechanical strength, but so far there are few reports on the alternating type aliphatic polyester amide in the literature, and there are problems such as difficulty in preparation and low molecular weight. A method for preparing an alternating type aliphatic polyester amide is to carry out a polycondensation reaction of an aliphatic diol containing an amide group and an aliphatic diacid, and a chain extender is usually used to react with a carboxyl group or a hydroxyl group to obtain a polymer with a higher molecular weight to improve the mechanical properties of the polyester amide. For example, Chinese patent application CN102643422A discloses a method for preparing a biodegradable alternating type aliphatic polyester amide, which uses an aliphatic diacid and a diamide diol for melt polycondensation to prepare an alternating type polyester amide prepolymer with both a terminal carboxyl group and a terminal hydroxyl group, and then uses a diacyl dilactam and a dioxazoline chain extender for joint chain extension to obtain a biodegradable alternating type aliphatic polyester amide with a characteristic viscosity of 0.30 to 0.59 dL / g. Although the molecular weight of the polyester amide obtained by using aliphatic diacids as reaction monomers is relatively high, side reactions such as acidolysis will occur during polymerization, resulting in low structural regularity of the polyester amide, which leads to problems such as low crystallization rate and long processing time. Another method for preparing alternating aliphatic polyester amides is to react aliphatic diacids with diamide diols, which can reduce the acidolysis side reaction during polymerization and obtain a highly regular polymer with high crystallinity and fast crystallization rate, but often with low molecular weight and poor mechanical properties.
[0004] Therefore, there is still a need for biodegradable alternating aliphatic polyester amides with good mechanical properties and improved crystallization properties. Summary of the invention The purpose of the present invention is to solve the problem that the biodegradable alternating aliphatic polyester amide in the prior art cannot take into account both mechanical properties and crystallization properties, and to provide a biodegradable alternating aliphatic polyester amide blend, a preparation method thereof and an application thereof.
[0006] According to one aspect of the present invention, a biodegradable alternating aliphatic polyester amide blend is provided, which comprises, based on 100 parts by weight of the blend, 45 to 80 parts by weight of a first biodegradable alternating aliphatic polyester amide; and 20 to 55 parts by weight of a second biodegradable alternating aliphatic polyester amide, wherein the first biodegradable alternating aliphatic polyester amide has an intrinsic viscosity in the range of 0.25 to 0.8 dL / g and a crystallization temperature in the range of 50 to 80°C, and the second biodegradable alternating aliphatic polyester amide has an intrinsic viscosity in the range of 0.1 to 0.22 dL / g and a crystallization temperature in the range of 90 to 120°C.
[0007] In some embodiments, the first biodegradable alternating aliphatic polyester amide and the second biodegradable alternating aliphatic polyester amide contain the same polyester amide repeating units.
[0008] In some embodiments, the polyester amide repeating unit has the following structure (I): in: R1 represents a linear, branched, cyclic, saturated or unsaturated carbon chain containing 0 to 8 carbon atoms; R2 represents a linear, branched, cyclic, saturated or unsaturated carbon chain containing 2 to 6 carbon atoms; R3 represents a linear, branched, cyclic, saturated or unsaturated carbon chain containing 0 to 8 carbon atoms; n represents the number of repeating units, which is in the range of 50-2000.
[0009] Preferably, based on 100 parts by weight of the biodegradable alternating aliphatic polyester amide blend, the blend comprises 45 to 70 parts by weight, or 50 to 60 parts by weight of the first biodegradable alternating aliphatic polyester amide.
[0010] Preferably, based on 100 parts by weight of the biodegradable alternating aliphatic polyester amide blend, the blend comprises 30 to 55 parts by weight, or 40 to 50 parts by weight of the second biodegradable alternating aliphatic polyester amide.
[0011] Preferably, the first biodegradable alternating aliphatic polyester amide has an intrinsic viscosity of 0.3 to 0.6 dL / g and a crystallization temperature of 60 to 70°C.
[0012] Preferably, the second biodegradable alternating aliphatic polyester amide has an intrinsic viscosity of 0.15 to 0.2 dL / g and a crystallization temperature of 100 to 110°C.
[0013] In some embodiments, the time it takes for the melt strip of the biodegradable alternating aliphatic polyester amide blend prepared according to GB / T1040.1-2006 to reach full setting by cooling with circulating water at 20°C is 80% shorter, preferably 99% shorter, than the time it takes for the melt strip of the first biodegradable alternating aliphatic polyester amide to reach full setting under the same conditions.
[0014] In some embodiments, the biodegradable alternating aliphatic polyester amide blend further comprises a functional additive, and the total amount of the functional additive is no more than 2.5 parts by weight based on 100 parts by weight of the blend.
[0015] In some embodiments, the functional auxiliary agent is selected from one or more of a compatibilizer, a plasticizer, a nucleating agent, and an antioxidant.
[0016] According to another aspect of the present invention, there is provided a method for preparing the above-mentioned biodegradable alternating aliphatic polyester amide blend, which comprises the following steps: The first biodegradable alternating aliphatic polyester amide, the second biodegradable alternating aliphatic polyester amide and an optional functional additive are blended according to the weight parts to prepare the biodegradable alternating aliphatic polyester amide blend.
[0017] In some embodiments, the blending method is selected from solution blending and melt blending, preferably melt blending.
[0018] According to another aspect of the present invention, there is provided use of the biodegradable alternating aliphatic polyester amide blend in film making, injection molding and spinning.
[0019] According to another aspect of the present invention, there is provided an article prepared from the biodegradable alternating aliphatic polyester amide blend.
[0020] The present invention obtains a biodegradable alternating aliphatic polyester amide with improved crystallization performance and good mechanical properties by blending two biodegradable alternating aliphatic polyester amides with different molecular weights and regularities in a certain proportion. The first biodegradable alternating aliphatic polyester amide has a high molecular weight and good mechanical properties, and can be blended with the second biodegradable alternating aliphatic polyester amide with a high regularity to induce co-crystallization of the blended polymers. The obtained blend has good crystallization performance while maintaining the original mechanical properties of the first aliphatic polyester amide, so that the processing time is significantly shortened, the production efficiency is significantly improved, and the biodegradable alternating aliphatic polyester amide resin market has huge commercial potential. BRIEF DESCRIPTION OF THE DRAWINGS The present invention is described in conjunction with the accompanying drawings so that those skilled in the art can better understand the various features and advantages of the present invention. In the accompanying drawings: Figure 1 It is a schematic diagram showing the DSC results of the first biodegradable alternating aliphatic polyester amide, the second biodegradable alternating aliphatic polyester amide and the blend of five biodegradable alternating aliphatic polyester amides obtained in Preparation Examples 1 to 7.
[0022] Figure 2 It is a schematic diagram showing the tensile test results of the first biodegradable alternating aliphatic polyester amide obtained in Preparation Examples 1 to 7 and five biodegradable alternating aliphatic polyester amide blends. DETAILED DESCRIPTION In order to make those skilled in the art further understand the present invention, the specific embodiments of the present invention are described in detail below. However, it should be understood that the embodiments of the present invention described are merely exemplary and the present invention is not limited to these embodiments.
[0024] According to one aspect of the present invention, a biodegradable alternating aliphatic polyester amide blend is provided, which comprises, based on 100 parts by weight of the blend, 45 to 80 parts by weight of a first biodegradable alternating aliphatic polyester amide; and 20 to 55 parts by weight of a second biodegradable alternating aliphatic polyester amide, wherein the first biodegradable alternating aliphatic polyester amide has an intrinsic viscosity in the range of 0.25 to 0.8 dL / g and a crystallization temperature in the range of 50 to 80°C, and the second biodegradable alternating aliphatic polyester amide has an intrinsic viscosity in the range of 0.1 to 0.22 dL / g and a crystallization temperature in the range of 90 to 120°C.
[0025] In the context of the present invention, "first biodegradable alternating aliphatic polyester amide" and "first aliphatic polyester amide" are used interchangeably, and "second biodegradable alternating aliphatic polyester amide" and "second aliphatic polyester amide" are used interchangeably.
[0026] In some embodiments, the first aliphatic polyester amide and the second aliphatic polyester amide contain the same polyester amide repeating units.
[0027] In some embodiments, the polyesteramide repeating unit has the structure of Formula (I): in: R1 represents a linear, branched, cyclic, saturated or unsaturated carbon chain containing 0 to 8 carbon atoms; R2 represents a linear, branched, cyclic, saturated or unsaturated carbon chain containing 2 to 6 carbon atoms; R3 represents a linear, branched, cyclic, saturated or unsaturated carbon chain containing 0 to 8 carbon atoms; n represents the number of repeating units, which is in the range of 50-2000.
[0028] In some embodiments, based on 100 parts by weight of the aliphatic polyester amide blend, the blend comprises 45 to 70 parts by weight, or 50 to 60 parts by weight of the first aliphatic polyester amide.
[0029] In some embodiments, based on 100 parts by weight of the aliphatic polyester amide blend, the blend comprises 30 to 55 parts by weight, or 40 to 50 parts by weight of the second aliphatic polyester amide.
[0030] Preferably, the aliphatic polyester amide blend comprises the first aliphatic polyester amide and the second aliphatic polyester amide in a weight ratio of 1:1.
[0031] In some embodiments, the first aliphatic polyester amide has an intrinsic viscosity of 0.3 to 0.6 dL / g and a crystallization temperature of 60 to 70°C.
[0032] In some embodiments, the second aliphatic polyester amide has an intrinsic viscosity of 0.15 to 0.2 dL / g and a crystallization temperature of 100 to 110°C.
[0033] Preferably, the intrinsic viscosity of the first aliphatic polyester amide is in the range of 0.3-0.6 dL / g and the crystallization temperature is in the range of 60-70°C, and the intrinsic viscosity of the second aliphatic polyester amide is in the range of 0.15-0.2 dL / g and the crystallization temperature is in the range of 100-110°C.
[0034] In the context of the present invention, the first aliphatic polyester amide has a relatively high molecular weight and a low regularity, while the second aliphatic polyester amide has a relatively high regularity and a low molecular weight. Therefore, in the context of the present invention, the first aliphatic polyester amide may also be referred to as "high molecular weight low regularity aliphatic polyester amide", and the second aliphatic polyester amide may also be referred to as "high regularity low molecular weight aliphatic polyester amide".
[0035] The preparation method of high molecular weight low regularity aliphatic polyester amide is well known to those skilled in the art. Generally speaking, the preparation steps include dissolving aliphatic diacid and diamide diol in a suitable solvent in a certain proportion, adding a suitable catalyst, heating to 140-190°C under the protection of an inert gas such as nitrogen, and continuing the reaction for 1-4 hours. Afterwards, the vacuum degree is gradually reduced to 3000-1400 Pa, while the temperature is raised to 160-200°C, and the reaction is continued for 3-10 hours to obtain a high molecular weight low regularity biodegradable alternating aliphatic polyester amide.
[0036] In some embodiments, the aliphatic diacid may be selected from succinic acid, adipic acid, sebacic acid, oxalic acid, and suberic acid.
[0037] In some embodiments, the diamide diol can be selected from N,N-bis(2-hydroxyethyl)adipamide, oxalamide diol, N,N-bis(2-hydroxybutyl)succinamide, N,N-bis(2-hydroxyhexyl)succinamide, N,N-bis(2-hydroxyoctyl)succinamide and N,N-bis(2-hydroxydecyl)succinamide.
[0038] Preferably, the molar ratio of the aliphatic diacid to the diamide diol may be 0.8 to 1.2, more preferably 0.9 to 1.05.
[0039] In some embodiments, the solvent may be selected from dimethyl sulfoxide, N,N-dimethylformamide, tetrahydrofuran and 1,4-dioxane, preferably dimethyl sulfoxide.
[0040] In some embodiments, the catalyst may be selected from stannous chloride, tin laurate, tetra-n-butyl titanate, and tetraisopropyl titanate, preferably stannous chloride.
[0041] In some embodiments, the catalyst is added in an amount of 0.05 to 0.15 wt % relative to the total amount of the aliphatic diacid and diamide diol reaction raw materials.
[0042] Preferably, in the synthesis of the first aliphatic polyester amide, a chain extender is also used, which is usually selected from isocyanates containing two or more functional groups and compounds containing two or more epoxy functional groups, such as isophorone diisocyanate, ethylene glycol diglycidyl ether, bisphenol F diglycidyl ether, polyethylene glycol diglycidyl ether.
[0043] The preparation method of high-tacticity low-molecular-weight aliphatic polyester amide is also well known to those skilled in the art. Generally speaking, the preparation steps include dissolving aliphatic diacid ester and diamide diol in a suitable solvent in a certain proportion, adding a suitable catalyst, heating to 140-190°C under the protection of an inert gas such as nitrogen, and continuing the reaction for 1-4 hours. Afterwards, the vacuum degree is gradually reduced to 3000-1400 Pa, while the temperature is raised to 160-200°C, and the reaction is continued for 3-10 hours to obtain a high-tacticity low-molecular-weight biodegradable alternating aliphatic polyester amide.
[0044] In some embodiments, the aliphatic diacid ester may be selected from dimethyl oxalate, dimethyl adipate, dimethyl adipate, and dimethyl sebacate.
[0045] In some embodiments, the diamide diol can be selected from N,N-bis(2-hydroxyethyl)adipamide, oxalamide diol, N,N-bis(2-hydroxybutyl)succinamide, N,N-bis(2-hydroxyhexyl)succinamide, N,N-bis(2-hydroxyoctyl)succinamide and N,N-bis(2-hydroxydecyl)succinamide.
[0046] Preferably, the molar ratio of the aliphatic diacid ester to the diamide diol may be 0.8 to 1.2, more preferably 0.9 to 1.05.
[0047] In some embodiments, the solvent may be selected from dimethyl sulfoxide, N,N-dimethylformamide, tetrahydrofuran and 1,4-dioxane, preferably dimethyl sulfoxide.
[0048] In some embodiments, the catalyst may be selected from tin catalysts such as stannous chloride, stannous acetate, stannous octoate, tin laurate, butyl stannoic acid and dibutyl tin oxide; titanium catalysts such as titanium isopropoxide and tetrabutyl titanate; antimony catalysts such as antimony trioxide, antimony acetate and antimony trichloride; and sulfonic acid catalysts such as p-toluenesulfonic acid, methanesulfonic acid and benzenesulfonic acid. Preferably, the catalyst is a titanium catalyst.
[0049] In some embodiments, the catalyst is added in an amount of 0.05 to 0.15 wt % relative to the total amount of the aliphatic diacid ester and diamide diol reaction raw materials.
[0050] In some embodiments, the time for the melt sample of the aliphatic polyester amide blend prepared according to GB / T 1040.1-2006 to reach full setting in a mold with circulating water cooling at 20°C is shortened by 80%, preferably 99%, compared with the time for the first aliphatic polyester amide melt sample to reach full setting under the same conditions.
[0051] In the context of the present invention, a polymer is "fully set" as the time required for a polymer melt strip prepared according to GB / T 1040.1-2006 to reach a hardness of at least 30 HD, as measured according to GB / T 2411-2008.
[0052] In some embodiments, the melt sample of the aliphatic polyester amide blend prepared according to GB / T 1040.1-2006 is cooled by circulating water at 20° C. for no more than 20 minutes, preferably no more than 10 minutes, more preferably no more than 5 minutes to achieve complete shaping.
[0053] In some embodiments, the melt sample of the first aliphatic polyester amide prepared according to GB / T 1040.1-2006 is cooled by circulating water at 20° C. for no less than 200 minutes to reach complete setting.
[0054] In some embodiments, the aliphatic polyester amide blend further comprises a functional additive selected from one or more of a compatibilizer, a plasticizer, a nucleating agent and an antioxidant, wherein the total amount of the functional additive does not exceed 2.5 parts by weight based on 100 parts by weight of the blend.
[0055] Examples of commercial products that can be used as compatibilizers include, but are not limited to, FUSABOND E588, Arkema AX8900, Arkema HX8290, and Dupont AC1125. Based on 100 parts by weight of the blend, the compatibilizer does not exceed 1 part by weight.
[0056] Examples of commercial products that can be used as plasticizers include, but are not limited to: DOW E588, DOW 1224AC, ARKEMA CP5001, SK 8605L. Based on 100 parts by weight of the blend, the compatibilizer does not exceed 1 part by weight.
[0057] Examples of commercial products that can be used as nucleating agents include, but are not limited to, Milliken Nx8000k, Milliken HPN20E, Clariant CAV102, and Adeka NA-21. Based on 100 parts by weight of the blend, the amount of the nucleating agent does not exceed 1 part by weight.
[0058] Examples of commercial products that can be used as antioxidants include, but are not limited to, Irganox 1010, Irganox 1076, and Irganox 168. The amount of the antioxidant is not more than 0.5 parts by weight based on 100 parts by weight of the blend.
[0059] According to another aspect of the present invention, there is provided a method for preparing the above-mentioned biodegradable alternating aliphatic polyester amide blend, which comprises the following steps: The first biodegradable alternating aliphatic polyester amide, the second alternating biodegradable alternating aliphatic polyester amide and an optional functional additive are blended according to the weight parts to prepare the biodegradable alternating aliphatic polyester amide blend.
[0060] In some embodiments, the blending method is selected from at least one of a solution blending method and a melt blending method.
[0061] The solution blending method comprises dissolving the first aliphatic polyester amide and the second aliphatic polyester amide in a suitable solvent in proportion, stirring and mixing them evenly, and then removing the solvent to obtain the biodegradable alternating aliphatic polyester amide blend.
[0062] The solvent used to dissolve the blend can be determined by those skilled in the art according to routine experiments, and is usually selected from dimethyl sulfoxide, N,N-dimethylformamide, tetrahydrofuran and dimethylacetamide.
[0063] The melt blending method comprises melting the first aliphatic polyester amide and the second aliphatic polyester amide in proportion at an appropriate temperature, stirring and mixing them evenly, and cooling them to obtain the biodegradable alternating aliphatic polyester amide blend.
[0064] The temperature for melting the blend can be determined by those skilled in the art based on routine experiments and is usually in the range of 45 to 85°C.
[0065] Preferably, the blending method is a melt blending method.
[0066] In some embodiments, the functional aid is selected from, for example, a compatibilizer, a plasticizer, a nucleating agent, an antioxidant, etc. The above description of the functional aid is also applicable here.
[0067] According to another aspect of the present invention, there is provided use of the biodegradable alternating aliphatic polyester amide blend in film making, injection molding and spinning.
[0068] The biodegradable alternating aliphatic polyester amide blend prepared according to the present invention can be applied to a variety of fields, such as but not limited to improving the cooling pelletizing of the biodegradable aliphatic polyester amide after synthesis, and being applied in the fields of film making, injection molding, spinning, etc. It has both the good mechanical properties of high molecular weight alternating aliphatic polyester amide and the good crystallization properties of high regularity alternating aliphatic polyester amide, significantly improving the processing properties of existing aliphatic polyester amide and expanding the application field.
[0069] According to another aspect of the present invention, there is provided an article prepared from the biodegradable alternating aliphatic polyester amide blend.
[0070] The product can be a film, a plastic part, a fiber, etc., and can be used in the fields of textile clothing, agricultural mulch film, fishing gear, plastic packaging bags, foam plastics, disposable tableware, disposable medical instruments, etc.
[0071] The descriptions of various features or implementation schemes in this application can be combined with each other if they are not contradictory, and all fall within the scope of protection requested by this application.
[0072] As used in the present application, “including” and “comprising” include both a case of consisting of only the included elements and a case of including other elements in addition to the included elements.
[0073] In the present specification and claims, numbers expressing temperatures, amounts, concentrations, percentages and the like are to be understood as being modified in all instances by the term "about".
[0074] Unless otherwise defined, all scientific and technical terms used in this application have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. When the definition of a term in this application conflicts with the meaning commonly understood by those skilled in the art to which the present invention belongs, the definition described in this application shall prevail.
[0075] Example The present invention will be further described below in conjunction with the embodiments so that those skilled in the art can fully understand the purpose, features and effects of the present invention. However, the protection scope of the present invention is not limited by the following embodiments.
[0076] Description of the raw materials used in the examples: Oxalic acid: purchased from Greagent, 99% (AR); Ethanolamine: purchased from Greagent, 99% (AR); Dimethyl adipate: purchased from Adamas, 99% (RG); Stannous chloride: purchased from Adamas, 99% (RG); Tetrabutyl titanate: purchased from Adamas, 99% (RG); Hexanediol diglycidyl ether: purchased from Adamas Company, epoxy value: 0.65-0.70 (RG); Methanol: purchased from Adamas, purity 99.9%; Dimethyl sulfoxide: purchased from Adamas Company, purity 99.9%.
[0077] The test methods and equipment descriptions of the main performance parameters in the embodiments are as follows: Intrinsic viscosity: measured using a viscometer model SYD-265B-1 from Shanghai Jingxi Instrument Manufacturing Co., Ltd. according to GB / T 1632.1-2008. DMSO was used as the solvent, the test temperature was controlled at 25±0.1°C, and the concentrations of the prepared solutions were 0.001 g / mL, 0.002 g / mL, 0.005 g / mL and 0.01 g / mL.
[0078] Thermal properties: The test was performed using a differential scanning calorimeter model Q200 from SP Industries according to GB / T19466.3-2004. During the test, 0.05 g of the sample to be tested was heated to 200°C at 10°C / min, kept at that temperature for 15 minutes to eliminate the thermal history, and then cooled to -50°C at 10°C / min to obtain the crystallization process curve of the sample.
[0079] Mechanical properties: measured using a tensile testing machine model 6800 from Instron according to ASTM D638. Polymer specimens were prepared using a press model yx-25 from Shanghai Xima Weili Rubber Machinery Co., Ltd. according to GB / T1040.1-2006.
[0080] The hardness was measured using a hardness tester model LX-D from Aliyiqi Company according to GB / T 2411-2008.
[0081] Preparation Example 1 200g of adipic acid and 250.79g of ethanolamine (molar ratio = 1:3) were added to a 1000mL reaction bottle for reaction, nitrogen was introduced, condensed water was turned off, the oil bath was heated to 180°C, timing was started, the reaction was performed for 12 to 14 hours, and then the temperature was lowered to room temperature. 400g of the initial product was added to 1200mL of methanol, heated to dissolve, filtered while hot, placed below -16°C for crystallization for 24 hours, directly filtered, washed with ice methanol, and dried to obtain 270g of N, N-bis (2-hydroxyethyl) adipamide (white powder), with a yield of 85%.
[0082] 100g of adipic acid and 144.32g of N, N-bis(2-hydroxyethyl) adipamide (molar ratio = 1.1:1) were put into a 500mL three-necked flask, and 0.244g of stannous chloride was added as a catalyst; first, the temperature was raised to 170°C for esterification reaction for 2 hours under nitrogen protection; then the temperature was gradually reduced to vacuum (<900Pa), the temperature was raised to 180°C for reaction for 3 to 5 hours, and then 13.2g of chain extender hexanediol diglycidyl ether was added under nitrogen protection, and the reaction was carried out at 180°C for 2 hours to obtain the first aliphatic polyester amide. The intrinsic viscosity thereof was measured by the aforementioned Ubbelohde viscometer method to be about 0.33dL / g.
[0083] Put 20g of the first aliphatic polyester amide into a flat mold, put the mold into a press, heat the press to 180°C, pressurize to 10MPa, hot press for 3 minutes, then cool with 20°C circulating water and hold the pressure for 3 minutes, release the pressure, and the raw material melt reaches a hardness of 30HD after about 240 minutes. After the sample is completely formed, take out the specimen from the mold.
[0084] Preparation Example 2 N, N-bis (2-hydroxyethyl) adipamide was prepared with reference to the above Preparation Example 1. Then 100g of dimethyl adipate and 133.19g of N, N-bis (2-hydroxyethyl) adipamide (molar ratio = 1:1) were put into a 500mL three-necked flask, and 0.233g of tetrabutyl titanate was added as a catalyst; first, under nitrogen protection, the temperature was raised to 170°C for esterification reaction for 2 hours; then the temperature was gradually reduced to vacuum (<900Pa), and the temperature was raised to 180°C for reaction for 3 to 5 hours to obtain the second aliphatic polyester amide. The intrinsic viscosity thereof was measured by the aforementioned Ubbelohde viscometer method to be about 0.18dL / g.
[0085] Put 20g of the second aliphatic polyester amide into a flat mold, put the mold into a press, heat the press to 180°C, press to 10MPa, hot press for 3 minutes, then cool with 20°C circulating water and hold the pressure for 3 minutes, release the pressure, the raw material melt immediately reaches a hardness of 30HD, and take out the specimen from the mold after the sample is completely formed.
[0086] Preparation Example 3 67 parts by weight of the first aliphatic polyester amide and 33 parts by weight of the second aliphatic polyester amide prepared above were put into a 250 mL three-necked flask, heated to 180° C. to melt under the protection of nitrogen, stirred vigorously (>4000 rpm) for 2 hours, and cooled to room temperature to obtain an aliphatic polyester amide blend.
[0087] Put 20g of the polyester amide blend into a flat mold, put the mold into a press, heat the press to 180°C, press to 10MPa, hot press for 3 minutes, then cool with 20°C circulating water and hold the pressure for 3 minutes, release the pressure, and the raw material melt reaches a hardness of 30HD after about 15 minutes. After the sample is completely formed, take out the specimen from the mold.
[0088] Preparation Example 4 60 parts by weight of the first aliphatic polyester amide and 40 parts by weight of the second aliphatic polyester amide prepared above were put into a 250 mL three-necked flask, heated to 180° C. to melt under the protection of nitrogen, stirred vigorously (>4000 rpm) for 2 hours, and cooled to room temperature to obtain an aliphatic polyester amide blend.
[0089] Put 20g of the polyester amide blend into a flat mold, put the mold into a press, heat the press to 180°C, press to 10MPa, hot press for 3 minutes, then cool with 20°C circulating water and hold the pressure for 3 minutes, release the pressure, the raw material melt reaches a hardness of 30HD after about 5 minutes, and take out the specimen from the mold after the sample is completely set.
[0090] Preparation Example 5 50 parts by weight of the first aliphatic polyester amide and 50 parts by weight of the second aliphatic polyester amide prepared above were put into a 250 mL three-necked flask, heated to 180° C. to melt under the protection of nitrogen, stirred vigorously for 2 hours, and cooled to room temperature to obtain an aliphatic polyester amide blend.
[0091] 20 g of the polyester amide blend was placed in a flat mold, and the mold was placed in a press. The press was heated to 180°C, pressurized to 10 MPa, and hot pressed for 3 minutes. Then, the press was cooled with 20°C circulating water and kept under pressure for 3 minutes. The pressure was released, and the raw material melt immediately reached a hardness of 30HD. After the sample was completely formed, the specimen was taken out of the mold.
[0092] Preparation Example 6 45 parts by weight of the first aliphatic polyester amide and 55 parts by weight of the second aliphatic polyester amide prepared above were put into a 250 mL three-necked flask, heated to 180° C. to melt under the protection of nitrogen, stirred vigorously for 2 hours, and cooled to room temperature to obtain an aliphatic polyester amide blend.
[0093] 20 g of the polyester amide blend was placed in a flat mold, and the mold was placed in a press. The press was heated to 180°C, pressurized to 10 MPa, and hot pressed for 3 minutes. Then, the press was cooled with 20°C circulating water and kept under pressure for 3 minutes. The pressure was released, and the raw material melt immediately reached a hardness of 30HD. After the sample was completely formed, the specimen was taken out of the mold.
[0094] Preparation Example 7 40 parts by weight of the first aliphatic polyester amide and 60 parts by weight of the second aliphatic polyester amide prepared above were put into a 250 mL three-necked flask, heated to 180° C. to melt under the protection of nitrogen, stirred vigorously for 2 hours, and cooled to room temperature to obtain an aliphatic polyester amide blend.
[0095] 20 g of the polyester amide blend was placed in a flat mold, and the mold was placed in a press. The press was heated to 180°C, pressurized to 10 MPa, and hot pressed for 3 minutes. Then, the press was cooled with 20°C circulating water and kept under pressure for 3 minutes. The pressure was released, and the raw material melt immediately reached a hardness of 30HD. After the sample was completely formed, the specimen was taken out of the mold.
[0096] Performance Testing The first aliphatic polyester amide, the second aliphatic polyester amide and the five aliphatic polyester amide blends obtained in the above-mentioned preparation examples 1 to 7 were subjected to DSC and tensile tests, and the results are shown in Figure 1 and Figure 2 , and are summarized in Table 1 below.
[0097] From the DSC results, it can be found that the first aliphatic polyester amide crystallizes very slowly, has a wide crystallization peak, and has a low crystallinity. With the addition of the second aliphatic polyester amide, the crystallinity and crystallization rate of the blend are significantly improved. The crystallinity and crystallization rate of the aliphatic polyester amide blend obtained in Example 5 are already substantially the same as those of the second aliphatic polyester amide, indicating that its processing properties are greatly improved. However, as the content of the second aliphatic polyester amide in the blend is further increased, the crystallinity and crystallization rate begin to deteriorate, as shown in the results of Examples 6 and 7.
[0098] The second aliphatic polyester amide has poor mechanical properties and cannot be subjected to tensile testing, so it is not shown in the chart. With the addition of the second aliphatic polyester amide, the mechanical properties of the blend first decrease and then gradually improve. The aliphatic polyester amide blends of Examples 4 and 5 are better than the first aliphatic polyester amide in tensile strength and elastic modulus. The aliphatic polyester amide after blending has both mechanical properties for practical applications and good processing properties. When the proportion of the second aliphatic polyester amide in the blend exceeds that of the first aliphatic polyester amide, the mechanical properties drop sharply. When the second aliphatic polyester amide reaches 60 parts by weight, the tensile strength of the blend even drops to less than 1MPa, as shown in the results of Examples 6 and 7. Table 1
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of the substantial technical content of the present invention. The substantial technical content of the present invention is broadly defined in the scope of the claims of this application. Any technical entity or method completed by others, if it is exactly the same as that defined in the scope of the claims of this application, or is an equivalent variation, will be deemed to be included in the scope of the claims of this application.
Claims
1. A biodegradable alternating aliphatic polyester amide blend, comprising, based on 100 parts by weight of the blend: 45 to 80 parts by weight of a first biodegradable alternating aliphatic polyester amide; and 20 to 55 parts by weight of a second biodegradable alternating aliphatic polyester amide; in, The first biodegradable alternating aliphatic polyester amide has an intrinsic viscosity in the range of 0.25 to 0.8 dL / g and a crystallization temperature in the range of 50 to 80°C, and the second biodegradable alternating aliphatic polyester amide has an intrinsic viscosity in the range of 0.1 to 0.22 dL / g and a crystallization temperature in the range of 90 to 120°C.
2. The blend according to claim 1, characterized in that The first biodegradable alternating aliphatic polyester amide and the second biodegradable alternating aliphatic polyester amide contain the same polyester amide repeating unit.
3. The blend according to claim 2, characterized in that The polyester amide repeating unit has the following formula (I): in: R1 represents a linear, branched, cyclic, saturated or unsaturated carbon chain containing 0 to 8 carbon atoms; R2 represents a linear, branched, cyclic, saturated or unsaturated carbon chain containing 2 to 6 carbon atoms; R3 represents a linear, branched, cyclic, saturated or unsaturated carbon chain containing 0 to 8 carbon atoms; n represents the number of repeating units, which is in the range of 50-2000.
4. The blend according to any one of claims 1 to 3, characterized in that The blend comprises 45 to 70 parts by weight, or 50 to 60 parts by weight of the first biodegradable alternating aliphatic polyester amide.
5. The blend according to any one of claims 1 to 4, characterized in that The blend comprises 30 to 55 parts by weight, or 40 to 50 parts by weight of the second biodegradable alternating aliphatic polyester amide.
6. The blend according to any one of claims 1 to 5, characterized in that The first biodegradable alternating aliphatic polyester amide has an intrinsic viscosity ranging from 0.3 to 0.6 dL / g and a crystallization temperature ranging from 60 to 70°C.
7. The blend according to any one of claims 1 to 6, characterized in that The second biodegradable alternating aliphatic polyester amide has an intrinsic viscosity ranging from 0.15 to 0.2 dL / g and a crystallization temperature ranging from 100 to 110°C.
8. The blend according to any one of claims 1 to 7, characterized in that It also contains functional additives, and the total amount of the functional additives is no more than 2.5 parts by weight based on 100 parts by weight of the blend.
9. The blend according to claim 8, characterized in that The functional auxiliary agent is selected from one or more of a compatibilizer, a plasticizer, a nucleating agent and an antioxidant.
10. The blend according to any one of claims 1 to 9, characterized in that The time for the melt sample of the aliphatic polyester amide blend prepared according to GB / T 1040.1-2006 to reach full setting by cooling with circulating water at 20° C. is at least 80% shorter than the time for the melt sample of the first biodegradable aliphatic polyester amide raw material to reach full setting under the same conditions.
11. A method for preparing the biodegradable alternating aliphatic polyester amide blend according to any one of claims 1 to 10, comprising the following steps: The first biodegradable alternating aliphatic polyester amide, the second alternating biodegradable alternating aliphatic polyester amide and an optional functional additive are blended according to the weight parts to prepare the biodegradable alternating aliphatic polyester amide blend.
12. The method according to claim 11, characterized in that The blending method is selected from a solution blending method and a melt blending method.
13. Use of the biodegradable alternating aliphatic polyester amide blend according to any one of claims 1 to 12 in film making, injection molding and spinning.
14. An article prepared from the biodegradable alternating aliphatic polyester amide blend according to any one of claims 1 to 13, preferably selected from the group consisting of films, plastic parts and fibers.
Citation Information
Patent Citations
Preparation method for biodegradable aliphatic alternating polyester amide
CN102643422A